2021
DOI: 10.1093/chromsci/bmab006
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination Between Fructus Gardeniae (ZZ) and Fructus Gardeniae Grandiflorae (SZZ) Based on Fingerprint Coupled with Chemometrics and Quantitative Analysis

Abstract: Fructus Gardeniae, known as Zhi-zi in China, has been used as Chinese herbal medicine and functional health food for thousands of years. Fructus Gardeniae Grandiflorae, named as Shui-zhizi, is a counterfeit herb of Fructus Gardeniae. In order to discriminate these two varieties, based on ultra-high-performance liquid chromatography, an analysis method of fingerprints of Fructus Gardeniae and Fructus Gardeniae Grandiflorae was established. With hierarchical clustering analysis and principal component analysis, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 24 publications
1
1
0
Order By: Relevance
“…PCA and OPLS-DA, as commonly used multivariate statistical analysis methods, can achieve sample classification. The content of 13 compounds in 25 batches of Zhizi and Shuizhizi was used for PCA analysis, and the results showed that 19 batches of Zhizi and 6 batches of Shuizhizi could be well distinguished ( Figure 3A ), consistent with prior studies ( Cao et al., 2021a ). In order to further understand which compounds have a significant contribution in distinguishing between Zhizi and Shuizhizi , those compounds datas were used for OPLS-DA analysis ( Figure 3B ).…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…PCA and OPLS-DA, as commonly used multivariate statistical analysis methods, can achieve sample classification. The content of 13 compounds in 25 batches of Zhizi and Shuizhizi was used for PCA analysis, and the results showed that 19 batches of Zhizi and 6 batches of Shuizhizi could be well distinguished ( Figure 3A ), consistent with prior studies ( Cao et al., 2021a ). In order to further understand which compounds have a significant contribution in distinguishing between Zhizi and Shuizhizi , those compounds datas were used for OPLS-DA analysis ( Figure 3B ).…”
Section: Resultssupporting
confidence: 84%
“…In recent years, advanced analytical methods such as ultra-flow liquid chromatography coupled with electrospray ionization triple quadrupole mass spectrometry (UFLC-Q-TRAP-MS/MS) and ultra-performance liquid chromatography (UPLC) have been employed for quantitative analysis and fingerprinting of Zhizi , providing insights into optimal harvesting times and quality evaluations from different regions ( Shan et al., 2019 ; Cao et al., 2021a ; Li et al., 2021 ). Additionally, researchers have utilized ultrahigh-performance liquid chromatography/quadrupole-orbitrap mass spectrometry (UHPLC/Q-Orbitrap MS) and UHPLC-triple quadrupole-linear ion trap mass spectrometry (UHPLC-QTRAP-MS) methods to identify thirteen differential markers and quantify metabolites in Zhizi and Shuizhizi , aiding in their differentiation ( Zhang et al., 2024 ).…”
Section: Introductionmentioning
confidence: 99%